2(x-2)+10(x+9)=

Simple and best practice solution for 2(x-2)+10(x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)+10(x+9)= equation:


Simplifying
2(x + -2) + 10(x + 9) = 0

Reorder the terms:
2(-2 + x) + 10(x + 9) = 0
(-2 * 2 + x * 2) + 10(x + 9) = 0
(-4 + 2x) + 10(x + 9) = 0

Reorder the terms:
-4 + 2x + 10(9 + x) = 0
-4 + 2x + (9 * 10 + x * 10) = 0
-4 + 2x + (90 + 10x) = 0

Reorder the terms:
-4 + 90 + 2x + 10x = 0

Combine like terms: -4 + 90 = 86
86 + 2x + 10x = 0

Combine like terms: 2x + 10x = 12x
86 + 12x = 0

Solving
86 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-86' to each side of the equation.
86 + -86 + 12x = 0 + -86

Combine like terms: 86 + -86 = 0
0 + 12x = 0 + -86
12x = 0 + -86

Combine like terms: 0 + -86 = -86
12x = -86

Divide each side by '12'.
x = -7.166666667

Simplifying
x = -7.166666667

See similar equations:

| 6x-5=13x+33 | | x^3=19x+30 | | 10v=-2 | | y=20+20x | | -10=s-(-6) | | 4log(4x)=12 | | X+17=204 | | 7s=-9 | | y=3x+-3 | | 10x-9=2x+11 | | (-3ln+6lnx)=6 | | 36*x^4=4.5 | | -5y+x=-3 | | x^2+0.106x-0.106=0 | | 9(x+2)=7x+25 | | 24=60-8x | | s-(-10)=2 | | 24=60-x | | 3x+12=6x+5 | | 4=16-n | | 4(2x+4)-13= | | 5x^3+21x^2-21x+5=0 | | 5(n+8)=10 | | 5x^2-5x-30=30 | | 50t+125=30t+200 | | 5x-x+4x=7-3 | | x+2.75=6 | | 7x-4=6.5 | | 9-6x=4-3x+3x | | 4-2x=14x+15 | | 2t+6=t+8 | | 0.5sin(2x)=cos(x) |

Equations solver categories